'A clash of two worlds'; disjuncture between the norms and values held by educational practitioners and parents of children with behavioural, emotional and social difficulties. (June 2014) - Broomhead, Karen
<x xml:space="preserve">Abstract</x> This article, by Karen Broomhead of Liverpool John Moores University, discusses an exploration of the clashing norms, values and expectations of parenting behaviours between parents of children with behavioural, emotional and social difficulties (BESD) and practitioners. Semi‐structured interviews with 15 education professionals, employed in both mainstream and BESD schools, highlighted how parents of children with BESD were deemed to experience chaotic, dysfunctional home circumstances, with no boundaries in place for their children. This contrasted with the structure, routine and stability that educational practitioners perceived themselves to provide for pupils with BESD. Practitioners employed in BESD schools elaborated on the perceived norms of chaos and dysfunction held by these parents, and suggested that these were evident due to an intergenerational continuity of ineffective parenting. Problematically, educational practitioners displayed a tacit acceptance of parental norms. This questioned whether advocating for pupils with BESD was at the top of the agenda for professionals, or whether a conflict‐avoidance strategy was adopted instead.